Phylogenetic relationship and characterization of the complete mitochondrial genome of Milionia basalis (Lepidoptera: Geometridae) - Du, Yimin (Mitochondrial DNA B Resour, 2019)
Larvae of the geometrid moth Milionia basalis feed exclusively on the podocarp tree, Podocarpus macrophyllus. In this study, we sequenced and analyzed the complete mitochondrial genome (mitogenome) of M. basalis. This mitogenome was 15,901 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and two ribosomal RNA unit genes (rRNAs). The whole mitogenome exhibited heavy AT nucleotide bias (82.2%). Gene order was conserved and identical to most other previously sequenced Geometridae. Most PCGs of M. basalis had the conventional start codons ATN, with the exception of nad1 (TTG) and cox1 (CGA). Except for four genes (cox1, cox2, nad5, and nad4) end with the incomplete stop codon T––, all other PCGs terminated with the stop codon TAA. Phylogenetic analysis showed that M. basalis got together with Apocheima cinerarius, Jankowskia athlete, and four Biston species (B. panterinaria, B. perclara, B. suppressaria, and B. thibetaria).